2017
DOI: 10.1016/j.seizure.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine valproate exposure is associated with alterations in hippocampal cell numbers and folate metabolism in a rat model of valproate teratogenicity

Abstract: This study shows that intrauterine VPA exposure is associated with changes in hippocampal cell numbers in the CA1/2 and CA3 region and in folate metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Prenatal VPA exposure of neuronal cultures from the cerebral cortices of prenatal mice embryos was shown to decrease the total number, total length, and complexity of neuronal dendrites [36]. Similarly, results obtained by Semmler et al [37] indicated that intrauterine VPA exposure caused dose-dependent neuronal cell number alterations in the hippocampal areas CA1/2 and the CA3 region and in folic acid metabolism in a rat model of valproate teratogenicity. On the other hand, VPA appears to cooperate in neuroprotection and cognitive enhancement by inhibition of histone deacetylase (HDAC) activity [38].…”
Section: Discussionmentioning
confidence: 85%
“…Prenatal VPA exposure of neuronal cultures from the cerebral cortices of prenatal mice embryos was shown to decrease the total number, total length, and complexity of neuronal dendrites [36]. Similarly, results obtained by Semmler et al [37] indicated that intrauterine VPA exposure caused dose-dependent neuronal cell number alterations in the hippocampal areas CA1/2 and the CA3 region and in folic acid metabolism in a rat model of valproate teratogenicity. On the other hand, VPA appears to cooperate in neuroprotection and cognitive enhancement by inhibition of histone deacetylase (HDAC) activity [38].…”
Section: Discussionmentioning
confidence: 85%
“…Numerous mechanisms have been proposed by which VPA may disrupt NT closure. These include epigenetic dysregulation ( Tung and Winn, 2010 ), inhibition of folate metabolism ( Fathe et al, 2014 , Roy et al, 2008 , Semmler et al, 2017 ), suppression of nitric oxide signalling ( Tiboni et al, 2013 , Tiboni and Ponzano, 2015 ) and increased reactive oxygen species production ( Akimova et al, 2017 , Tung and Winn, 2011 ). In addition, VPA's anti-acetylation effects may disrupt post-translational modifications of other effector proteins including those involved in actin regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the molecular mechanism of action of this drug, a recent study performed in a rat model of teratogenesis showed that intrauterine VPA exposure caused a decrease in the number of astrocytes in the developing hippocampus. This study also explored the mechanistic role of this molecule and found that VPA produced an increase in the concentration of 5‐methyl‐tetrahydrofolate (THF) in the brain of newborn pups, suggesting a role of VPA on folate metabolism (Semmler et al, ). Moreover, another study showed conclusively that VPA interfered with the EMT of NCCs in culture, thereby suggesting the role of VPA as a potent NC teratogen (Fuller, Cornelius, Murphy, & Wiens, ).…”
Section: Chemical Agentsmentioning
confidence: 99%